I'am learning about-eid-ul-fitr - Khan, Saniyasnain (Goodword books, New Delhi, 2002)
"Eid, which means 'happiness' is the most joyous festival of the Muslim calendar. Eid-ul-Fitr is the first day after the month-long fasting of Ramadan. Muslims throughout the world prepare for this day. They give food and money to the poor. They clean their homes, wear their best clothes and prepare special sweets for the family and friends. They also attend special Eid prayers in the mosque or in an open area. This little book on Eid-ul-Fitr tells the story of two young children living in London -- how they celebrate their Eid by visiting the mosque, meeting their friends, eating delicious food, and enjoying carnival rides. And how their parents explain to them the true meaning of Eid-ul-Fitr"--Page 4 of cover